A Novel Dual Authenticated Encryption Scheme Suitable for Social Networking Services - Han-Yu Lin (Applied Sciences, 2019)
Nowadays there are many social networking services supporting three-party communication such as Skype, Line, and Facebook Messenger. To ensure the message security, a cryptographic encryption scheme is a commonly adopted measure. However, the traditional asymmetric encryption only allows one designated recipient to decrypt the ciphertext with his/her private key. It is thus difficult for two parties to share the same ciphertext without exposing their private keys. In this paper, the author comes up with a novel dual authenticated encryption (DAE) scheme designed for three-party communication environments. Specifically, a DAE scheme enables a party to generate a single ciphertext that could be solely decrypted by the other two participants without sharing their private keys. It is also formally shown that the proposed scheme achieves the crucial security properties using the random oracle proof model.